Mapping the bathymetry of coral islands with the Landsat series: Quantitative evaluation of the consistency and temporal change detection - Yongming Liu; Shilin Tang; Yuye Huang; Qidong Chen; Longhai Xiong; Sufen Wang (International Journal of Applied Earth Observations and Geoinformation)
Landsat series data (Landsat-5 Thematic Mapper (TM), Landsat-7 Enhanced Thematic Mapper Plus (ETM+), Landsat-8 Operational Land Imager (OLI), and Landsat-9 OLI2) hold significant potential for detecting temporal changes of underwater terrain in optically shallow waters resulting from earthquakes, volcanic eruptions, waves, and human activities due to their extensive time series (nearly 40 years) and medium-spatial-resolution (30 m). However, different Landsat series images have different band sets and signal-to-noise ratios (SNRs) which may impact the consistency of the bathymetry inversion results of optimization-based bathymetry inversion models. Therefore, this study initially quantitatively evaluated the consistency of Landsat series data-derived bathymetry data over the South China Sea, which has a notable distribution of coral islands. The results of 12 images indicated that the root mean square error values of the estimated water depth are generally less than 4 m at Qilian Yu and less than 2 m at Dongsha Dao at depths shallower than 10 m. At depths greater than 10 m, OLI/OLI2 obtained higher accuracy in water depth inversion than did TM/ETM+. The inter-comparison results and temporal results of different geomorphic zones indicated that the Landsat series-derived water depth values in the reef flat and shallow lagoon, where water depth is shallower than 10 m, exhibit high consistency. However, because TM and ETM+ have lower SNRs, for deep lagoons and fore reefs where water depth is greater than 10 m and the substrate is dark, the OLI/OLI2- and TM/ETM+-derived water depth values substantially differ. Then, Landsat series data were applied to detect bathymetric changes in the Nanwei Dao. The temporal results of Nanwei Dao show that the depth of the new port has increased from approximately 2.00 to 10.00 m, whereas the new land in the northeast region has changed from a depth of approximately 7.50 m to land. To date, approximately 584252.74 ± 228884.43 m3 of sediment has been excavated in the port area of Nanwei Dao, with 1010657.21 ± 897737.97 m3 of land reclaimed from the water. Overall, the Landsat series data can be used to detect temporal changes in the underwater terrain of coral islands in the range of approximately 0 to 10 m over the South China Sea for nearly 40 years, and achieving reliable 40-year long-term monitoring of water depths exceeding 10 m remains challenging.